KONSTRIBUSI KEMAMPUAN MERANCANG PEMBELAJARAN TERHADAP EFEKTIVITAS PEMBELAJARAN DOSEN STKIP-PGRI SUMATERA BARAT - Edi Suarto (STKIP Pesisir Selatan, 2016)
This study aims to reveal the contribution Designing Learning Ability Of Education Lecturers Efektigitas STKIP-PGRI West Sumatra. The hypothesis of the study is a contribution to effective learning capabilities designed an instructional faculty PGRI-STKIP West Sumatra, West. This study uses a total sampling involving subjects were 71 lecturers. They are professors and lecturers PNSD Foundation. Data were collected through questionnaires and student grades. The data collected is then analyzed statistically using correlation and regression analysis. Results of the analysis showed that: The ability to design learning has a significant contribution to the effectiveness of learning lecturer PGRI-STKIP West Sumatra amounting to 35.5%, based on above findings, it can be concluded that the ability to design learning contribute to the effectiveness of instructional faculty STKIP PGRI Sumatra.